Role Media Social and Good Corporate Governance (GCG) to Management Zakat at the Institution Baitul Mall Aceh (BMA) - Rohamah Rohamah; Ichsan Ichsan; Quratul Aini; Muliana Muliana; Sakinah Mawaddah; Salimah Salimah (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research aims to ascertain the impact of social media and good corporate governance (GCG) on zakat management at Baitul Mal Aceh (BMA). This study employs a qualitative methodology with a descriptive orientation. This research focuses on analyzing the marketing strategy employed by Baitul Mal Aceh in their zakat collection and distribution program. The research methodology employed in this study is library research, specifically the collection of Baitul Mal data and other relevant information by extensive examination of existing books and periodicals. Research findings demonstrate that GCG (Good Corporate Governance) has yielded significant advantages for companies by means of efficient management and the utilization of interaction networks, such as social media, which greatly facilitate global outreach and the formulation of strategies for the allocation and administration of zakat funds from BMA.